Serum Amylase Activity and its Correlation with Serum Calcium and Albumin - Pokhrel, Nabaraj; Shrestha, Usha; Jha, Bharat (Nepal Journal of Science and Technology, 2010)
This study was performed in the pathology department of OM Hospital and Research Centre Pvt. Ltd. In this study, amylase, calcium and albumin concentrations in blood serum of 99 subjects visiting this hospital were determined using standard protocol. Out of 99 subjects, 42 were female and 57 were male. Serum amylase activity was found normal in 47% males and 57% females, serum level calcium was found normal in 57% males and 38% females and serum level of albumin was found normal in 61% males and 73% females. The correlation between total corrected calcium and amylase was found slightly positive (r=0.01). But the correlation between total corrected calcium and albumin and albumin and amylase were found slightly negative (r = -0.33 and -0.06 respectively). The study also revealed that low levels of amylase and calcium can be obtained in significant number of subjects. Key Words: Blood serum; Amylase; Albumin; OM hospital DOI: 10.3126/njst.v10i0.2960 Nepal Journal of Science and Technology Vol. 10, 2009 Page: 195-198